(untitled) (Canadian Medical Education Journal, 2017)
Background: Poverty is a key determinant of health that leads to poor health outcomes. Although most healthcare providers will work with patients experiencing poverty, surveys among healthcare students have reported a curriculum gap in this area. This study aims to introduce and evaluate a novel, student-run interprofessional inner city health educational program that combines both practical and didactic educational components. Methods: Students participating in the program answered pre- and post-program surveys. Wilcoxon signed-rank tests and descriptive thematic analysis were used for quantitative and qualitative data, respectively. Results: A total of 28 out of 35 participants responded (response rate: 80%). Student knowledge about issues facing underserved populations and resources for underserved populations significantly increased after program participation. Student comfort working with underserved populations also significantly increased after program participation. Valued program elements included workshops, shadowing, and a focus on marginalized populations. Conclusion: Interprofessional inner city health educational programs are beneficial for students to learn about poverty intervention and resources, and may represent a strategy to address a gap in the healthcare professional curriculum.